Triage-HF plus: 12-month study of remote monitoring pathway for triage of heart failure risk initiated during the Covid-19 pandemic. (14th October 2021) - Bachtiger, P; Park, S; Letchford, E; Scott, F; Barton, C; Ahmed, F Z; Cole, G; Keene, D; Plymen, C M; Peters, N S
Abstract: Background: The Covid-19 pandemic necessitated rapid adoption of remote monitoring across cardiovascular patient cohorts. Most patients with cardiac implantable electronic devices (CIEDs) are now able to be remotely monitored using either scheduled, patient- or threshold-triggered transmissions. The validated "Triage Heart Failure Risk Score" (Triage-HFRS) is a medical algorithm within company-specific CIEDs that can risk-stratify patients as low-, medium- or high-risk of worsening heart failure (WHF) in the next 30 days based on integrated monitoring of physiological parameters. Building on a previous proof-of-concept of the Triage-HF Plus pathway, we integrated remote data with simple 5-question telephone triage within a clinical pathway to identify WHF during the first year of the Covid-19 pandemic. Purpose: Prospective evaluation of clinical remote monitoring pathway integrating Triage-HFRS with protocolised telephone triage (Triage-HF Plus pathway). Methods: Prospective, real-world evaluation of clinical pathway serving a large urban region over a 12-month period, using data from April 2020 to April 2021 (initiated during the first wave of Covid-19 pandemic in the UK). From a population of 435 patients with CIEDs, 87 "high" Triage-HFRS alerts were received and patients contacted for telephone triage assessment. Screening questions were designed to identify episodes of WHF and non-HF events. Intervention was at discretion of the clinical practitioner and in line with guideline-directed practice. A consecutive sample of 115 "medium" risk scores received the same triage. Results: Successful contact was made with 72 (82.8%) high-risk patients. Classification for high scoring patients confirmed on triage included isolated heart failure (18.3%), heart failure concurrent to medical problem (5.7%), alternative medical problem (10.3%), and recent hospital admission (8.0%); triage reassured absence of acute cause of high score in 40.2%. The sensitivity and specificity for detection of WHF was 87.9% (0.77–0.99) and 59.4% (0.50–0.69) respectively. Positive and negative predictive values were 40.3% and 94.0%, respectively. Overall accuracy was 66.2%. Conclusions: The Triage-HF Plus pathway served as a useful remote monitoring tool for identifying patients with WHF whose care had been otherwise disrupted by the Covid-19 pandemic, allowing timely intervention and cementing the longer-term role for such models of care delivery. Crucially, in this multimorbid, high-cost population, relevant non-HF issues were also identified. The high negative predictive value further highlights the potential of proactive surveillance over conventional, periodic follow up. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Imperial Health Charity